Kitchen safety virtual tour: Hazard Identification Training Tool (VT-HITT) innovation - Saad, Mazni; Mohamad Najib, Muhammad Danial Haiqal; Pratt, Thomas James; Nazir, Faridah; Md Sawari, Siti Salwa; Mokhtar, Mohd Khalid (2022)
The rise in the number of workers in gastronomy tourism has coincided with an increase in occupational workplace accidents. New workers lack hazard identification abilities and fail to recognize dangerous events in the workplace. Consequently, a two-fold goal has been established: (1) To design and develop Augmented 360-degree panoramas for spotting risks in the kitchen workplace, (2) To validate the effectiveness of VT-HiTT applications for spotting risks in the kitchen workplace. The invention involved the 360-degree camera (GoPro Fusion). The VT-HiTT application was validated by 10 experts consisting of IT, safety officers, and culinary lecturers. Through open-ended questions in a Google Form, experts gave the VR application a high validation score for both face and content validity. These validations contain usefulness, ability, and overall relevance as a practice format and simulator experience. The effectiveness of this VT-HiTT innovation was then validated through interviews with seven experienced executives and managers at various levels from various nations. In conclusion, the findings of this study are noteworthy in demonstrating that hazard identification may be accomplished using VT- HiTT. This application is useful in the teaching and learning of kitchen-related and suitable to explain hazards in the kitchen. The teaching and learning with VT-HiTT applications will be easier to understand and fun.